(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The article is devoted to the study of the problem of assessing and forecasting the stability of competitive positions of agricultural enterprises. The analysis of theoretical approaches to the definition of the studied categories is carried out. Based on the essence of the competitive position, a methodical approach to assessing the competitive position of an agricultural enterprise is substantiated: a method of comparing the rate of change of the main economic indicators of an agricultural enterprise and the industry as a whole is proposed. The article calculates the forecast values of the integrated stability index of the competitive position and its components using the method of exponential smoothing using the Brown-Mayer model, which allowed to assess the dynamics and trends of agricultural enterprise. A model is proposed, which can not only assess the level of competitive position of the enterprise, but also identify areas of change in the level of competitive position of the enterprise as a whole and in terms of individual components, develop conceptual frameworks for effective management decisions.